Critical review of the methodology for assessing farm-level grain losses after harvest - Boxall, R A (Tropical Development and Research Institute LondonGB, 1986)
Discusses all aspects of post-harvest grain loss assessment including definition of terminology and the post harvest system, objectives of loss assessment projects and their requirements such as finance, equipment, manpower etc. Describes various techniques for assessing losses which occur during harvesting, threshing, drying, and milling. Highlights principal agents for loss during grain storage such as insects, vertebrate pests, and microorganisms and discusses techniques for measuring loss caused by these agents. Discusses sampling as it relates to loss assessment studies and role of such studies in loss reduction.